MIKROENKAPSULASI EKSTRAK KULIT BUAH NAGA MERAH DENGAN TEKNIK SPRAY DRYING - Mira Sofyaningsih; Iswahyudi Iswahyudi (UHAMKA PRESS, 2018)
The use of synthetic food coloring and food coloring that are prohibited, because they have an adverse effect on health, is still prevalent in food and beverage production. Red dragon fruit skin which has been a waste can be used for the production of natural dyes because the proportion of the skin is quite large and contains anthocyanin pigments. The purpose of this study was to study the microencapsulation method of red dragon fruit peel extract using maltodextrin DE10-12 with spray drying technique. The spray drying process was carried out at an inlet temperature of 150-160ºC and outlet temperature of 70-80ºC and DE10-12 maltodextrin concentration of 10, 15, and 20%. From the results of the study, it was known that the concentration of 20% has the highest yield (40.59%), the lowest water content (4.67%), and the highest brightness level (76.77). Keywords: Lightness, Microencapsulation, Moisture Content, Red Dragon Fruit Skin, Yield